ACTIVE LISTENING AND OTHERNESS TO RELEASE FORGIVENESS FORGIVENESS THROUGH MEDIATION - Stefany, Alana; Ribeiro, Geovanna; Rodrigues, Thiago; Souza, Welma C.; Souza, Vanessa; Magalhães, Hellen Pereira Cotrim (CIPEEX, 2022)
THE IMPORTANCE OF ACTIVE LISTENING AND OTHERNESS IN THE MEDIATION PROCEDURE AS AN EFFECTIVE TECHNIQUE FOR DECIDING SOCIAL CONFLICTS AND A PLACE OF FORGIVENESS LIBERATION. TO CONDUCT THIS STUDY, A DEDUCTIVE HYPOTHESIS METHOD WAS APPLIED (LINS & MARTINS, 2018). AS A MAIN ASPECT OF THE DISCUSSION, THE IMPORTANCE OF KNOWING HOW TO LISTEN IS HIGHLIGHTED AS A WAY TO CAUSE EMPATHY AND, ABOVE ALL, TO CONSTITUTE A MORE LOVING ENVIRONMENT CONDUCIVE TO THE SEARCH FOR MORE SATISFACTORY SOLUTIONS TO CONFLICTS. THE IMPORTANCE OF OTHERNESS IS ALSO PRESENTED AS THE EFFECTIVE VISION AND PERCEPTION OF THE OTHER, HENCE THE RELEASE OF THE SO-CALLED FORGIVENESS, AS A CHANCE FOR RECONCILIATION, THE CHANGE OF CONFLICTING RELATIONSHIPS, AND THE AWAKENING TO A SOFTER AND MORE PEACEFUL SOCIETY. TO OBTAIN THE EXPECTED ANSWERS, THEFOLLOWING SPECIFIC OBJECTIVES WERE ELABORATED: A) TO IDENTIFY FACTS AND RELATIONSHIPS THAT CAUSE CONFLICT; B) TO DECIPHER EVERYTHING THROUGH A NON-VERBALIZED CODIFICATION; C) TO CONFIGURE OR REDEFINE COMMUNICATION IN THE WAY THAT EVERYONE NEEDS, IN A TRANSPARENT AND DISCREET WAY. THUS, THE FOLLOWING QUESTIONS WERE CREATED AS GUIDING QUESTIONS FOR THIS ANALYSIS: ARE THE VITAL INTERESTS OF THE IMPORTANT PARTIES AND THOSE WITH WHOM THEY MUST RESPOND RESPECTED, OR AT LEAST NOT VIOLATED? DO MEDIATORS HAVE RESPONSIBILITIES IN TRYING TO RECONCILE THE PARTIES OR TRANSMUTE THE DISPUTE TO ACHIEVE THE END GOAL? MEDIATORS SHOULD CREATE AN ATMOSPHERE OF TRUST THAT FACILITATES CONFLICT RESOLUTION. ALTHOUGH THE PARTICIPANTS REMAINED UNDER THE INFLUENCE OF FEELINGS OF ANGER, DISAPPOINTMENT, FRUSTRATION AND REVENGE? FROM THE STUDY CARRIED OUT, IT IS OBSERVED THAT THE EXERCISE OF ACTIVE LISTENING CAN BE CONSIDERED A FUNDAMENTAL TOOL, AS IT HELPSIN ESTABLISHING RELATIONSHIPS WITH OTHERS, IN RESOLVING CONFLICTS, IN UNDERSTANDING THE FEELINGS AND OPINIONS OF OTHERS, BECAUSE DIALOGUE IS WHAT SUSTAINS THE HUMAN BEING, AND SOCIAL EXISTENCE, THEREFORE, MUST BE BASED ON RESPECT AND COOPERATION. IN THIS SENSE, ACTIVE LISTENING IN MEDIATION ENCOURAGES THOSE INVOLVED IN A CONFLICT TO EXPRESS THEIR FEELINGS AND ENCOURAGES THE PARTIES TO LISTEN TO EACH OTHER, LEAVING NO ROOM FOR RELATIONSHIPS THAT REINFORCE FEAR AND AGGRESSIVENESS. IN THIS SENSE, IT IS NECESSARY TO WELCOME THE OTHER, WHICH ALLOWS FOR OPENNESSTO OTHERNESS. TO CONCLUDE, IT IS NOTED THAT THE OBJECTIVE PRESENT IN THE SURVEY WAS FULLY ACHIEVED AND THE RESPONSE TO THE INITIAL QUESTIONS SIGNALS THAT MEDIATION IS A DEMOCRATIC FORM OF CONFLICT MANAGEMENT, BUT NOT ALL AGREEMENTS REACHED DURING THE MEDIATION SESSION ARE TRULY REPRESENTATIVE OF FORGIVENESS, BECAUSE THEY CAN ONLY EXPRESS THE DESIRE TO END A DISPUTE.